ChemInform Abstract: Enantiocatalytic Activity of Substituted 5‐Benzyl‐2‐(pyridine‐2‐yl)imidazolidine‐4‐one Ligands. Issue 35 (8th August 2013) - Drabina, Pavel; Karel, Sergej; Panov, Illia; Sedlak, Milos
Abstract The copper(II) complexes of newly synthesized chiral ligands (I) are studied as enantioselective catalysts for the Henry reaction.